Influences of Isolated Probiotics on Total Essential Amino Acid Profile of Fresh Water Fish Cyprinus Carpio - K.PARVATHI; J. KARTHEGAA (International Journal of Pharma and Bio Sciences, 2018)
Aquaculture is developing and intensifying in most part of the world in response to the increasing demand for aquatic food products. Protein is essential for normal function, growth and maintenance of body tissues. Amino acids are the building blocks of proteins. Aquatic animal fish is a vital dietary source of good quality animal proteins and amino acids and therefore play an important role in human nutrition. The probiotics are defined as live microbial feed supplements which beneficially affect the host species by improving their intestinal microbial balance. The first application of probiotics occurred in 1986, to test their ability to increase growth of hydrobionts (organisms that live in water). Isoleucine is a branched chain essential amino acid and is required for muscle development and proper growth. Fish muscle tissue has an abundance of amino acids and flavors and is highly digestible. The common carp (Cyprinus carpio) has been one of the oldest domesticated species of fish for food. Carp are omnivorous in nature. The increased total essential amino acid profile was recorded in the fish fed with combined probiotics Bacillus sp. and Lactobacillus sp. then compared with the fish fed with single probiotics Bacillus sp. and with the control group at the end of an experiment 39.77 ± 0.15 on 150th day in experimental pond II. The present results reveal that total essential amino acid profile was significantly increased in experimental II (pond C) fed with combined probiotics. The aim of the present study was to find out the influences of isolated probiotics on total essential amino acid profile of fresh water fish Cyprinus carpio.